Improving Paragraph Writing Competence through an Inquiry Method Using Audio Media - Gusni, Gusni (Education and Talent Development Center Indonesia (ETDC Indonesia), 2023)
The implementation of learning to write paragraphs through the inquiry method using audio media shows a change in behavior in learning in a positive direction. This proves that the application of the inquiry method using audio media can improve the ability to write student paragraphs, both argumentative paragraphs and persuasive paragraphs. Changes in student behavior can be seen in the creative abilities and skills of students who experience changes from cycle I to cycle II. In cycle I, students generally did not really understand paragraphs and were not able to write paragraphs properly and correctly. In cycle II, students understood paragraphs well and students were able to write good and correct paragraphs. The results of the study show that the application of the inquiry method using audio media can increase learning to write paragraphs. The results of the overall test analysis from cycle I to cycle II showed an increase. Starting from the assessment of the cognitive, affective, to psychomotor domains, it shows an increase.